Gender Inequality Index –Conceptual Analysis - Remani, Salini (International Journal of Psychosocial Rehabilitation, 2020)
Gender inequality remains a major barrier to human development. Girls and women have made major strides since 1990, but they have not yet gained gender equity. The disadvantages facing women and girls are a major source of inequality. All too often, women and girls are discriminated against in health, education, political representation, labour market, etc.—with negative consequences for development of their capabilities and their freedom of choice.